PENGEMBANGAN LKPD BERBASIS (HOTS) PADA PELAJARAN TEMATIK KELAS VI SEKOLAH DASAR ISLAM NW LENDANG BUNG - Aziz, Abdul; Muh. Thala'at; Siti Hamidah (Al-mujahidah, 2022)
The type of research used in the research and development or R&D which aims to determind the feasibility of HOTS based LKPD media for the thematic lesson that wil be developed. This research uses the ADDIE model which consists of 5 step analysis, design, development, implementation, and evaluation sheets and student response questionnaires. The Result of the HOTS based thematic LKPD research show that the development results are very suitable for use in thematic learning. This is based on the results of media experts getting 95 in the interval X>92,28 with very good categories and validation from material experts getting 94 in the interval meanwhile, in the limited field trial, 5 people as respondents got an average scor of 65,2 at the interval is in the interval X>58,74 it can be seen that the HOTS –based thematic LKPD media is in the very good category. So the final conclusioncan be drawn that the development of HOTS based LKPD is very suitable for use as a learning medium in thematic lessonsin class VI Islamic Elementary School NW Lendang Bunga.